Use of Medicaid and housing data may help target areas of high asthma prevalence. (16th March 2017) - Vesper, Stephen; Robins, Thomas; Lewis, Toby; Dombkowski, Kevin; Wymer, Larry; Villegas, Rebeca; Batterman, Stuart
ABSTRACT: Objective : To determine if there was a significant difference between mold contamination and asthma prevalence in Detroit and non-Detroit Michigan homes, between newer and older homes, and if there is a correlation between mold contamination and measures of Medicaid use for asthma in the 25 Detroit zip codes. Methods : Settled dust was collected from homes ( n = 113) of Detroit asthmatic children and from a representative group of Michigan homes ( n = 43). The mold contamination for each home was measured using the Environmental Relative Moldiness Index (ERMI) scale and the mean ERMI values in Detroit and non-Detroit homes were statistically compared. Michigan Medicaid data (13 measures related to asthma) in each of the 25 zip codes in Detroit were tested for correlation to ERMI values for homes in those zip codes. Results : The mean ERMI value (14.5 ± 8.0) for Detroit asthmatic childrens' homes was significantly (Student's t -test, p < 0.001) greater than the mean ERMI value (2.1 ± 6.2) for the non-Detroit homes. Detroit homes > 60 years old had significantly ( p = 0.01) greater mean ERMI values than Detroit homes ≤ 60 years old (15.87 vs. 11.25). The percentage of children that underwent spirometry testing for their persistent asthma (based on Medicaid data) was significantly, positively correlated with the mean ERMI values of the homes in the 25 zip codes. Conclusions : Applying Medicaid-use data for spirometry testing and locating a city's older housing stock might help find foci of homes with high ERMI values.